HARMONISASI REGULASI HUKUM NASIONAL DAN HUKUM INTERNASIONAL TERHADAP INDUSTRI KELAPA SAWIT INDONESIA YANG BERDAMPAK PADA PERUBAHAN IKLIM GLOBAL - Amalia, Selma Dwi (Zhata Institut, 2024)
Indonesia is the country with the largest palm oil commodity in the world. This can be proven by the extensive palm oil plantations throughout Indonesia, especially in the provinces of Riau, West Kalimantan, Central Kalimantan, North Sumatra and East Kalimantan. However, the palm oil industry actually has a negative impact on the environment, because every stage of palm oil processing can produce gasses that cause greenhouse gasses. Indonesia feels a dilemma with the presence of international regulations in the Paris Agreement. On the one hand, there is Indonesia's push to ratify the agreement and support the global greenhouse gas reduction mission. But on the other hand, the Indonesian palm oil industry is a contributor to the country's foreign exchange which can improve the Indonesian economy. By using normative juridical methods through a statutory approach, and an analytical approach, the author finds two problem formulations (1) harmonization of national law and international law regarding Indonesia's main palm oil export commodity, (2) the role of the Indonesian government in implementing the ratified agreement regarding climate change international. Keywords: Palm Oil, Paris Agreement, and Climate